Syntrophic effect of indigenous and inoculated microorganisms in the leaching of rare earth elements from Western Australian monazite - Corbett, M.; Eksteen, Jacques; Niu, X.; Watkin, Elizabeth (2018)
© 2018 Institut Pasteur The unique physiochemical properties exhibited by rare earth elements (REEs) and their increasing application in high-tech industries has created a demand for secure supply lines with established recovery procedures that create minimal environmental damage. Bioleaching experiments conducted on a non-sterile monazite concentrate with a known phosphate solubilising microorganism (PSM) resulted in greater mobilisation of REEs into solution in comparison to experiments conducted on sterile monazite. By combining the native consortia with an introduced PSM, a syntrophic effect between the populations effectively leached a greater amount of REEs than either a single PSM or the indigenous population alone. With sterile monazite, Penicillium sp.CF1 inoculated experiments released a total REE concentration of 12.32 mg L -1 after incubation for 8 days, whereas on non-sterile ore, double the soluble REE concentration was recorded (23.7 mg L -1 ). Comparable effects were recorded with Enterobacter aerogenes, Pantoea agglomerans and Pseudomonas putida. Alterations in the microbial populations during bioleaching of the monazite ore were determined by diversity profiling and demonstrated noticeable changes in community inhabitants over 14 days. The presence of native Firmicutes on the monazite appears to greatly contribute to the increased leaching recorded when using non-sterile monazite for REE recovery.